2009
DOI: 10.1186/1750-9378-4-s1-s2
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer disparities in Black men of African descent: a comparative literature review of prostate cancer burden among Black men in the United States, Caribbean, United Kingdom, and West Africa

Abstract: BackgroundAfrican American men have the highest prostate cancer morbidity and mortality rates than any other racial or ethnic group in the US. Although the overall incidence of and mortality from prostate cancer has been declining in White men since 1991, the decline in African American men lags behind White men. Of particular concern is the growing literature on the disproportionate burden of prostate cancer among other Black men of West African ancestry in the Caribbean Islands, United Kingdom and West Afric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
173
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(184 citation statements)
references
References 17 publications
8
173
1
Order By: Relevance
“…[1] There seems to be a paucity of evidence regarding the epidemiology of prostate cancer in sub-Saharan Africa. [2][3] It is, however, known that men of African descent appear to suffer disproportionately more from prostate cancer compared with men of other races or ethnicities, [4] and present with more advanced disease. [5][6][7][8] To date most, if not all, of the epidemiological studies on prostate cancer in South Africa (SA) have been undertaken by Heyns and colleagues in the Western Cape Province, [5,[9][10][11][12][13] and their findings have influenced national guidelines and policy.…”
mentioning
confidence: 99%
“…[1] There seems to be a paucity of evidence regarding the epidemiology of prostate cancer in sub-Saharan Africa. [2][3] It is, however, known that men of African descent appear to suffer disproportionately more from prostate cancer compared with men of other races or ethnicities, [4] and present with more advanced disease. [5][6][7][8] To date most, if not all, of the epidemiological studies on prostate cancer in South Africa (SA) have been undertaken by Heyns and colleagues in the Western Cape Province, [5,[9][10][11][12][13] and their findings have influenced national guidelines and policy.…”
mentioning
confidence: 99%
“…Additional observations have shown that stem cells are also located in different regions of the prostate, which have the ability to survive androgen ablation and can regenerate prostatic tissue after androgen is replaced (Goto et al, 2006). The prolonged regenerative capacity of prostate progenitor stem cells may increase their susceptibility to accumulate genetic or epigenetic alterations during their life cycle, events that may help to promote increased proliferative rates, decreased cell death, and overall survival advantages over prostate progenitor stem cells, contributing thus to transformation (Al-Hajj & Clarke, 2004;Bapat et al, 2005;Beachy et al, 2004;Miller et al, 2005;Mimeault & Batra, 2006b, 2007aOdedina et al, 2009). The tumor associated stem cell compartment may therefore, represent a self-replicating reservoir of malignant cells, which may accumulate further genetic and epigenetic aberrations that can thus result in therapy-resistant, tumor recurrence and/or metastasis (Hsieh et al, 2007;Rajan et al, 2009;Witte, 2009).…”
Section: Stem Cells In the Prostatementioning
confidence: 99%
“…The transatlantic slave trade transported approximately 15 million people from West Africa to Europe, the Americas and the Caribbean during the 15 th to 19 th centuries (29). That number does not include the many millions who died en route.…”
Section: Prostate Cancer In People Of African Descentmentioning
confidence: 99%